The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3389/fphar.2011.00065
|View full text |Cite
|
Sign up to set email alerts
|

Re-Evaluation of Nicotinic Acetylcholine Receptors in Rat Brain by a Tissue-Segment Binding Assay

Abstract: Nicotinic acetylcholine receptors (nAChRs) of the cerebral cortex and cerebellum of rats were evaluated by a radioligand binding assay, employing tissue segments, or homogenates as materials. [3H]-epibatidine specifically bound to nAChRs in rat cortex or cerebellum, but the dissociation constants for [3H]-epibatidine differed between segments and homogenates (187 pM for segments and 42 pM for homogenates in the cortex and 160 pM for segments and 84 pM for homogenates in the cerebellum). The abundance of total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…In particular, the decrease in binding was greater for [ 3 H]‐NMS‐binding (more than 10% reduction) than for [ 3 H]‐CGP‐12,177‐binding sites (20–50% reduction) in the three regions. This preliminary result implies that many airway samples should be pooled in the case of homogenate binding, and that homogenization causes a large loss in yield of airway tissue receptors, similar to other tissues and radioligands (Tanaka et al., 2004; Wang et al., 2011).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In particular, the decrease in binding was greater for [ 3 H]‐NMS‐binding (more than 10% reduction) than for [ 3 H]‐CGP‐12,177‐binding sites (20–50% reduction) in the three regions. This preliminary result implies that many airway samples should be pooled in the case of homogenate binding, and that homogenization causes a large loss in yield of airway tissue receptors, similar to other tissues and radioligands (Tanaka et al., 2004; Wang et al., 2011).…”
Section: Resultsmentioning
confidence: 93%
“…Regardless of the presence or absence of cartilage, the airway segments were directly incubated with radioligands in physiological solution. As epithelial and muscle layers were not scraped from the cartilage, and in contrast to a marked reduction of [ 3 H]‐NMS and [ 3 H]‐CGP‐12,177 binding in homogenates (Figure 2), the present segment binding assay is less prone to loss of receptors and to modification of the natural environment/conformation of the receptors (Wang et al., 2011). However, the airway segments used in the present study were heterogeneous tissues that included various types of cells, as shown in Figure 1.…”
Section: Discussionmentioning
confidence: 96%
“…The 6 mL of filter count scintillation cocktail (Perkin-Elmer Life Science, Boston, MA) was added to each vial and radioactivity was counted by Tri-Carb Liquid Scintillation Counter (Perkin-Elmer Life Science, Boston, MA). The 10G 5 M concentration of nicotine bitartrate was used for non-specific binding 20 . Muscarinic and nicotinic receptor binding inhibition data were presented as B/B 0 (%) (transformed from the cpm counts of the tested compounds) and means of logarithmic concentrations±standard error of the mean of four to six experiments conducted in duplicate.…”
Section: Studymentioning
confidence: 99%